A new three-dimensional (3D) multilayer organic material : synthesis, swelling, exfoliation, and application - Xu, Lu (2013)
A novel fully rigid, rod-shaped oligo(p-benzamide) (OPBA-6) molecule was designed and synthesized, which can be recrystallized into a three-dimensional (3D) multilayer material via an antiparallel molecular packing model. Intermolecular hydrogen bonding and π–π interaction are brought to ensure a strong intralayer interaction, while decoration of layer surface with sulfonic groups promotes water to enter interlayer space and facilitates the swelling and exfoliation of sample. With a simple dispersion in water, the obtained multilayer material can be easily swollen by water without destruction of in-plane morphology and subsequently delaminated into 2D nanosheets with thickness of about 5.38 nm. This achievement may be the first attempt to exfoliate layered organic materials and thus provide a new strategy to prepare 2D organic nanosheets without using any substrates or templates as required by conventional and widely used self-assembly routes. Based on exfoliated nanosheets, poly(vinyl alcohol) nanocomposites were prepared using a simple water solution processing method. A 64% increase in tensile stress and a 63% improvement in Young’s modulus were achieved by addition of 7 wt % OPBA-6 loading.